Influence of the Compressible Flexographic Sleeve Exploitation on Print Quality - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2021)
Due to the nature of the used materials, the quality of the flexographic print depends on a large number of process parameters and the materials parameters in all the phases of the production. During the pre-press, sleeves and stickyback tapes are needed for the mounting of the printing forms. These two components in the process of the flexographic printing are the least researched ones, even though they have a potentially significant impact on the stability and the quality of the printing process, as well as the print quality itself. Therefore, this research is oriented towards the investigation of the influence of the compressible sleeve exploitation on the process and print quality parameters through the measurement of optical density, tone value increase and trapping. The aim of the research is the improvement of stability and predictability of the printing process and print quality through the defining of the intensity and the trends of changes in densitometric parameters of quality.
Keywords: densitometry; exploitation; flexographic sleeve; print quality; printing process stability; INKS